PENGARUH PEMBERIAN BEBERAPA DOSIS BIO-SLURRY SEBAGAI PUPUK ORGANIK DAN PENJARANGAN BUAH TERHADAP PERTUMBUHAN DAN HASIL TANAMAN STROBERI - Gabriella Nathalia; Agus Sulistyono; Djarwatiningsih Djarwatiningsih (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2023)
The production of strawberry plants decreases every year because strawberry farmers do not optimize strawberry cultivation techniques. The purpose of this study was to determine the effect of bio-slurry dose and the number of fruit on the growth and yield of strawberry plants. This research was conducted in Ringin Agung, Medowo Village, Kandangan District, Kediri Regency, East Java from November 2021 – March 2022. The study used a two-factor Randomized Block Design (RBD) which was repeated three times. The first factor was the dose of bio-slurry which consisted of 9 levels: NPK (Control), 750 g, 1,000 g, 150 ml, 200 ml, 750 g + 150 ml, 750 g + 200 ml, 1,000 g + 150 ml, 1,000 g + 200 ml. The second factor is fruit thinning which consists of 2 levels: fruit thinning and without fruit thinning. Results showed that the treatment of organic bio-slurry fertilizer at a dose of 1000 g + 200 ml liquid was able to supply nutrients equivalent to NPK fertilizer. The dose of bio-slurry 1000 g + liquid 200 ml and fruit thinning improved the quality and production of strawberries.